2019
DOI: 10.1109/tgrs.2019.2901396
|View full text |Cite
|
Sign up to set email alerts
|

Improved Statistically Based Retrievals via Spatial-Spectral Data Compression for IASI Data

Abstract: In this paper we analyze the effect of spatial and spectral compression on the performance of statistically based retrieval. Although the quality of the information is not completely preserved during the coding process, experiments reveal that a certain amount of compression may yield a positive impact on the accuracy of retrievals. We unveil two strategies, both with interesting benefits: either to apply a very high compression, which still maintains the same retrieval performance as that obtained for uncompr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
(70 reference statements)
1
3
0
Order By: Relevance
“…Results revealed that the classification accuracy was still reliable after the compression stage, even at high compression ratios. Similar conclusions were yielded for anomaly detection [12], [13] for linear spectral unmixing [14], [15], and for statistical retrieval algorithms [16]- [18]. To the best of our knowledge, a similar study on the impact of compression on image segmentation has not been presented.…”
Section: Introductionsupporting
confidence: 67%
“…Results revealed that the classification accuracy was still reliable after the compression stage, even at high compression ratios. Similar conclusions were yielded for anomaly detection [12], [13] for linear spectral unmixing [14], [15], and for statistical retrieval algorithms [16]- [18]. To the best of our knowledge, a similar study on the impact of compression on image segmentation has not been presented.…”
Section: Introductionsupporting
confidence: 67%
“…• Accounting for noisy and spatial features. Recently, in [8,9], great improvement in the performance of retrieval methods was reported when applying standard compression algorithms to the images. Although this result may appear counterintuitive since compression implies reduction on the amount of information in the images, a certain level of compression is actually beneficial because: 1) compression removes information but also noise, and it could be useful to remove the components with low signal-to-noise ratio (SNR); and 2) spatial compression introduces information about the neighbouring pixels in an indirect yet simple way.…”
Section: Introductionmentioning
confidence: 99%
“…In the latter case, it can be stated that, e.g., lossy compression should not lead to sufficient reduction of image classification accuracy (although even in this case "sufficient" can be described quantitatively). Here, it is worth recalling that considerable attention has been paid to the classification of lossy compressed images [17,[26][27][28][29][30][31][32][33]. It has been shown that lossy compression can sometimes improve classification accuracy or, at least, the classification of compressed data provides approximately the same classification accuracy as classification of uncompressed data [34][35][36].…”
Section: Introductionmentioning
confidence: 99%